Research on muck conditioning for EPB shield tunnelling in composite formation - Yalong Jiang; Xin Tang; Bitang Zhu; Kai Zhou; Yucong Pan; Changjie Xu (Scientific Reports)
Abstract Compared with simple formations, EPB (earth pressure balance) shield tunnelling in composite formations encounters severe problems with muck conditioning and require improved muck conditioning technology to fulfil expectations for continuous and efficient excavation. In the Nanchang Metro Line 4 Project, a water-rich sand-argillaceous siltstone composite formation is encountered. With a high moisture content and complex composite formation ratio, it is quite difficult to determine the optimum muck conditioning scheme, and thus, muck spewing accidents frequently occur during the tunnelling process. In this study, laboratory muck conditioning tests are conducted for five ratios of stratum, from a full section water-rich sand formation to a water-rich sand-argillaceous siltstone composite formation. The muck conditioner ratio for EPB shield tunnelling in such composite formations is dynamically optimized based on an analysis of propulsion speed, penetration rate, thrust force and torque of the shield machine in the field. The following muck conditioning scheme is obtained: (1) For the full-section water-rich sand layer, foam and bentonite slurry should have similar proportions, namely, the foam injection ratio is 10–15% and the bentonite slurry injection ratio is 10%. (2) As the argillaceous siltstone content increases from 10 to 90%, the foam injection rate gradually increases from 20 to 50%, and the bentonite slurry injection rate gradually decreases from 20% to 0. (3) If the argillaceous siltstone content is 10%, then CMC polymer with an injection ratio of 1% is required. Once the argillaceous siltstone content exceeds 70%, it is necessary to add mudstone dispersant solution (1:5) with a volume ratio of 2 to 3%. According to the analysis of the field tunnelling parameters, including penetration rate, total shield thrust and cutterhead torque, the optimization of the muck conditioning scheme proposed based on laboratory tests is proved effective and deserves further application.